The Process and Outcome of the Africanization of Honey Bees in Mexico: Lessons and Future Directions - Guzman-Novoa, Ernesto; Morfin, Nuria; De la Mora, Alvaro; Macías-Macías, José O.; Tapia-González, José M.; Contreras-Escareño, Francisca; Medina-Flores, Carlos A.; Correa-Benítez, Adriana; Quezada-Euán, José Javier G. (Frontiers in Ecology and Evolution, 2020)
The Africanization of honey bees (Apis mellifera L.) in the Americas is among the most extensive insect invasions in the world, with large-scale effects on the economy and ecology of a whole continent. Africanized honey bees (AHBs) are a distinctive lineage of A. mellifera, resulting of the extensive admixture between African subspecies (A. m. scutellata and A.m. adansoni) with resident European stocks of honey bees introduced into the Americas. Despite its great importance, to date, the outcome of Africanization of honey bees has not been evaluated in detail. In this article we use the case of Mexico, one of the top beekeeping countries in the world, to assess the effects of Africanization of honey bees and its outcome. There is evidence of African genes in honey bee populations across Mexico, with prevalence in the tropical areas and less so in temperate ones. The Africanization of honey bees resulted in lower honey yields per hive in temperate climates of Mexico, but this has not been assessed in the tropical regions. Mexico’s total honey production and exports at the start of the Africanization process decreased, but today, they have partially rebounded and have remained stable. As in all countries where Africanization has occurred, the defensive behavior of honey bees in Mexico increased but notably, stinging incidents involving humans have been relatively insignificant (0.23 fatalities per million people). Ecologically, AHBs seem to have posed limited impact on the native apifauna and have contributed to pollination of major economic crops, but more studies are needed to evaluate the overall effect. AHBs can be potentially more resistant to parasites and diseases and worth of note is that AHBs in Mexico resulted in a new generation of beekeepers that propelled management and selective breeding. In general, the evidence suggests that the Africanization of honey bees in Mexico has had a less severe impact than originally predicted. We suggest some lines for future directions that may help to better understand the effects, make sustainable use and ameliorate the negative characteristics of AHBs.